Virtual reality: aplikasi teknologi untuk peningkatan kunjungan wisatawan - Sri Hartini; Cathleya Anglelyn; Sukaris Sukaris (STIE Perbanas Surabaya, 2019)
The development of Indonesia's tourist destinations when supported by technological advances. With a destination, technology can be known and visited. One influence of technology is a virtual reality in the context of destinations. Virtual reality is a technology that allows users to interact with the environment in a virtual world that is simulated by a computer, so users feel they are in that environment. Focus on consumer behavior in choosing tourist destinations associated with virtual reality. Specifically, the research objective is to determine the effect of presence in virtual reality, on perceived enjoyment, attitude toward Virtual reality, and intention to visit destinations. The study population was tourists in East Java, with a purposive sampling method. Samples were asked to play virtual reality in destinations that had never been visited, then they answered questionnaires related to their experiences using virtual reality. The analysis tool uses SEM-PLS. The results show five proposed hypotheses, four hypotheses were accepted and one hypothesis was rejected. Presence influences perceive enjoyment, but presence does not affect attitudes toward virtual reality. Perceive enjoyment influences attitudes toward virtual reality and intention to visit tourist destinations. Attitudes toward virtual reality affect the intention to visit tourist attractions